Exploring advanced nanostructures and functional materials for efficient hydrogen storage: a theoretical investigation on mechanisms, adsorption process, and future directions - Jana, Gourhari; Chattaraj, Pratim Kumar (Frontiers in Chemistry, 2025)
Hydrogen is a promising candidate for renewable energy storage and transportation due to its high energy density and zero carbon emissions. Its practical applications face challenges related to safe, efficient storage and release systems. This review article investigates advanced nanostructured materials for hydrogen storage, including metal acetylide and cyanide complexes, B,N-doped γ-graphyne nanotubes (γ-GNT), lithium-phosphide double helices, and Ni-decorated carbon-based clusters. Density Functional Theory (DFT) based computations are used to analyze binding energies, thermodynamic stability, and adsorption mechanisms. Ni-decorated C12N12 nanoclusters demonstrate enhanced storage capacities, binding up to eight H2 molecules with a favorable N-(μ-Ni)-N configuration. Lithium-phosphide double helices show potential for 9.6 wt% hydrogen storage within a stable, semiconducting framework. Functionalization of γ-GNT with OLi2 at boron-doped sites significantly enhances storage potential, achieving optimal hydrogen binding energies for practical applications. Additionally, metal acetylide and cyanide complexes, stabilized by noble gas insertion, display thermodynamically favorable hydrogen adsorption. These results highlight the potential of these functionalized nanostructures for achieving high-capacity, reversible hydrogen storage. The nanostructures in this study, such as γ-graphyne nanotubes (γ-GNT), lithium-phosphide double helices, metal acetylide and cyanide complexes, and Ni-decorated carbon-based clusters, are selected based on their ability to exhibit complementary hydrogen adsorption mechanisms, including physisorption and chemisorption. γ-GNT offers high surface area and tunable electronic properties, ideal for physisorption enhanced by heteroatom doping. Lithium-phosphide double helices facilitate Kubas-like chemisorption through unsaturated lithium centers. Metal acetylide and cyanide complexes stabilize hydrogen adsorption via charge transfer and conjugated frameworks, while Ni-decorated clusters combine polarization-induced physisorption. These materials represent a strategic approach to addressing the challenges of hydrogen storage through diverse and synergistic mechanisms. The review also addresses challenges and outlines future directions to advance hydrogen’s role as a sustainable fuel.